Giant cell leiomyoma with red, hydropic and cystic degeneration: a case report - Nicol Lopez Ovando (Gaceta Médica Boliviana, 2020)
Uterine myomas are fairly common neoplasms, classified according to their location in the myometrium: subserosal, intramural, transmural and submucosal. In turn, there are different morphological variants and degenerative changes that are a frequent phenomenon in myomas, especially the larger they are, such as apoplexy, atrophy, hyalinisation, red degeneration, cystic degeneration, peripheral calcification, necrosis, hydropic degeneration and malignant or sarcomatous degeneration. We report the case of a 53 year old female patient who underwent laparotomy where a tumour mass of 8150 grams was identified. The anatomopathological result was a giant leiomyoma with 3 different types of degeneration: red, hydropic and cystic. This case is reported due to the rarity of its conformation and the lack of reports in world literature. This is the first case presented and allows us to make some comments on the pathology.